Study of Social Support and Factors Affecting Efforts Improving The Quality of Life of Patients with Pulmonary Tuberculosis - Pariyana; Iche Andriyani Liberty; Muhammad Aziz (Sriwijaya Journal of Medicine, 2020)
Study of Social Support and Factors Affecting EffortsImproving the Quality of Life for Patients with Lung Tuberculosis.Tuberculosis (TB) is an infectious disease caused by the bacterium Mycobacterium tuberculosis. Decrease in the quality of life of tuberculosis patients can have a negative impact on the continuity of therapy which causes failure of therapy. The quality of life of pulmonary TB patients is important to be assessed in various aspects ranging from the aspects of physical well-being, psychology, social and environmental relations. The purpose of this study was to examine social support and influencing factors influencing efforts to improve the quality of life of pulmonary TB patients. This type of research is observational research using cross sectional design. The study population was all pulmonary tuberculosis patients in Palembang City. This study received a total sample of 111 people. The quality of life was measured by the Indonesian WHOQOL-BREFF questionare instrument and the results were obtained by univariate, bivariate, and multivariate analysis using the SPSS 22 program. Of the 111 study respondents, a good percentage of the quality of life of tuberculosis patients in Palembang City Health Center was 71.17% and the not good at 28.83%. There was no significant relationship between demographic characteristics (age, sex, body mass index, education level, employment status, and marital status), blood pressure, history of diabetes, and history of smoking with quality of life. There is a significant relationship between treatment duration. family support. friend support. and community support with the quality of life of tuberculosis patients (p value <0.05). Patients with tuberculosis with poor family support have the opportunity to have a poor quality of life of 86.18%.